The Useful of Water Glass as Preservative on Salted Egg Quality - Imam Thohari; Susrini Idris; Dewi Saptarini Yuliandari (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2008)
The materiasl used were duck eggs and curing agent. The research method used was factorial experiment (2x4) Randomized Block Design with two treatment factors. The first factors was preservation which consisted of two levels namely : with (P1) and without (Po) dipping in water glass as preservative. The second factor was the length of storage which consisted of four levels namely : 0 day (L0), 14 days (L14), 28 days (L28) and 42 days (L42). Each treatment was devided into three groups based on the time of salting. The variables measured were microbial load, protein content and organoleptic qualities (flavour, colour of yolk and texture) of salted eggs. The result of statistical analysis showed that a highly significant different effect (P<0.01) of the length of storage on the microbial load, preservation and the length of storage on protein content and a significant effect (P<0.05) of the preservation and the combination treatments on the microbial load, the flavour and colour of yolk of salted eggs. The salted eggs experienced off flavour, changed yolk colour, and texture while storage for 28 days, neverthless panelist prefered its. The conclusion that the dipping in water glass as preservative and the different length of storage in room temperature affected on microbial load, protein content and organoleptic qualities (flavour, the colour of yolk and the texture). Dipping in water glass as preservative would make salted egg's microbial load lower than the ones without preservative. A longer storage could increase the microbial load and decrease protein content. After 28 days of storage the egg's flavour and texture as well as yolk colour started to change, however, the panelist preferred its. It was suggested that never keep the salted egg preserved with water glass solution more than 28 days at room temperature. Keywords: salted egg, water glass